Heterogeneity of Skill Needs and Job Complexity: Evidence from the OECD PIAAC Survey - Konstantinos Pouliakas; Giovanni Russo (Institute for the Study of Labor (IZA), 2015)
We use information from the new OECD Survey of Adult Skills (PIAAC) to investigate the link between job tasks and cognitive skill demand in 22 advanced economies. Skill demand is operationalized by the assessed literacy and numeracy skills of workers with well-matched skills to their job duties. Jobs are categorised according to the nature of tasks, including the intensity of abstract reasoning, employee latitude, interactivity or manual work. The analysis confirms the significant relation between task complexity and higher skill needs. The significant relation holds independently of the endogenous supply of formal human capital, occupational or industrial structure and other job or individual characteristics. The results confirm the (indirect) mapping between tasks and skills as predicted by the task approach to labour economics. Given the marked heterogeneity in workplace practices adopted by employers, it is clear that enterprise level workplace development policies are warranted as enablers of skills matching and higher labour productivity.
Keywords: J24; M12; M54; 330; skills; tasks; skill demand; job complexity; PIAAC; mismatch